Binding Orientations and Lipid Interactions of Human Amylin at Zwitterionic and Anionic Lipid Bilayers - Zhenyu Qian; Yan Jia; Guanghong Wei (Journal of Diabetes Research)
Increasing evidence suggests that the interaction of human islet amyloid polypeptide (hIAPP) with lipids may facilitate hIAPP aggregation and cause the death of pancreatic islet β-cells. However, the detailed hIAPP-membrane interactions and the influences of lipid compositions are unclear. In this study, as a first step to understand the mechanism of membrane-mediated hIAPP aggregation, we investigate the binding behaviors of hIAPP monomer at zwitterionic palmitoyloleoyl-phosphatidylcholine (POPC) bilayer by performing atomistic molecular dynamics simulations. The results are compared with those of hIAPP at anionic palmitoyloleoyl-phosphatidylglycerol (POPG) bilayers. We find that the adsorption of hIAPP to POPC bilayer is mainly initiated from the C-terminal region and the peptide adopts a helical structure with multiple binding orientations, while the adsorption to POPG bilayer is mostly initiated from the N-terminal region and hIAPP displays one preferential binding orientation, with its hydrophobic residues exposed to water. hIAPP monomer inserts into POPC lipid bilayers more readily than into POPG bilayers. Peptide-lipid interaction analyses show that the different binding features of hIAPP at POPC and POPG bilayers are attributed to different magnitudes of electrostatic and hydrogen-bonding interactions with lipids. This study provides mechanistic insights into the different interaction behaviors of hIAPP with zwitterionic and anionic lipid bilayers.